2010
DOI: 10.1371/journal.pntd.0000814
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Visceral Leishmaniasis in Albania: A Retrospective Analysis of 1,210 Consecutive Hospitalized Patients (1995–2009)

Abstract: BackgroundLittle information is available about infantile visceral leishmaniasis (VL) in Albania as regards incidence, diagnosis and management of the disease.Methodology/Principal FindingsDemographic data, clinical and laboratory features and therapeutic findings were considered in children admitted to University Hospital of Tirana from 1995 to 2009, and diagnosed as having VL. The diagnosis was based on bone-marrow microscopy/culture in 77.5% of patients, serology in 16.1%, and ex juvantibus in 6.4%. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 22 publications
5
37
0
1
Order By: Relevance
“…Positive findings like pallor, splenomegaly, hepatomegaly were observed but less common than to the Dash S et al 7 and Hamid GA et al 18 Visceral leishmaniasis should be strongly suspected in patients with unexplained fever, being longer than 2 weeks, pallor, splenomegaly, hepatomegly and potential exposure in an endemic area or from areas from where On complete blood count (CBC), the majority of patients had anemia, leucopenia, and thrombocytopenia (90%, 67.5% and 72.5%, respectively) followed by neutropenia (27.5%), and lymphocytosis (65%). Similar finding were observed by various authors such as Dash S et al 7 , Singh K et al, 12 and Petrela R et al 20 series have reported a normocytic normochromic anemia in peripheral smear examination. 11,13,14 In this study we observed normocytic normochromic and anisocytosis hypochromic in equal frequency (35%) followed by anisopoikilocytosis hypochromia (20%), normocytic hypochromia (5%) and anisopoikilocytosis normochromic (2.5%).…”
Section: Discussionsupporting
confidence: 89%
“…Positive findings like pallor, splenomegaly, hepatomegaly were observed but less common than to the Dash S et al 7 and Hamid GA et al 18 Visceral leishmaniasis should be strongly suspected in patients with unexplained fever, being longer than 2 weeks, pallor, splenomegaly, hepatomegly and potential exposure in an endemic area or from areas from where On complete blood count (CBC), the majority of patients had anemia, leucopenia, and thrombocytopenia (90%, 67.5% and 72.5%, respectively) followed by neutropenia (27.5%), and lymphocytosis (65%). Similar finding were observed by various authors such as Dash S et al 7 , Singh K et al, 12 and Petrela R et al 20 series have reported a normocytic normochromic anemia in peripheral smear examination. 11,13,14 In this study we observed normocytic normochromic and anisocytosis hypochromic in equal frequency (35%) followed by anisopoikilocytosis hypochromia (20%), normocytic hypochromia (5%) and anisopoikilocytosis normochromic (2.5%).…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, in a recent study, Phlebotomus perniciosus and Phlebotomus neglectus , both competent vectors of L. infantum [9], were found in the same region, with the highest abundance recorded in July and August [10]. This explains the common onset of the disease during the summer, as reported in other studies carried out in the Mediterranean region [4-6]. …”
Section: Lettersupporting
confidence: 56%
“…In this case, collecting information on the summer stay of the child at a seaside locality, apparently one of the commonest habits of middle class families in this part of Italy, eventually turned out to be pivotal anamnestic data, leading physicians to the correct interpretation of clinical and laboratory findings. In Italy, as well as in other southern European countries, the majority of patients diagnosed and treated for VL are indeed children aging under or equal to 3 years [4-6], due to the immaturity of their immune system [7]. Noteworthy, the name ‘ infantum ’ was initially attributed to this Leishmania species for causing a visceral syndrome predominantly in infants in the Mediterranean region.…”
Section: Lettermentioning
confidence: 99%
“…In contrast, lymphadenopathy is very common (72%) among children with VL in Sudan (Siddig et al 1990) that shares the same etiologic agent (L. donovani) as Ethiopia. On the other hand, Mediterranean paediatric VL (caused by Leishmania infantum) is characterised by low prevalence of lymphadenopathy (0% among Sicilian patients; Cascio et al 2002), 11% among Albanian patients (Petrela et al 2010). This difference remains unexplained.…”
Section: Discussionmentioning
confidence: 99%